The right to education in Nigeria : an analysis of the law and policy - Hussein, Folorunsho Ahmad (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2016)
Right to education is a recognised right within the context of the International Human Rights Instruments. Basic education is also considered a fundamental right of children in most of those instruments. Nations were therefore on this ground encouraged by the United Nations to consider right to basic education a fundamental right by domesticating the Convention on the Rights of the Child (CRC) in order to advance the promotion of children's right to basic education in their respective domestic levels. For this reason, Nigeria as one of the signatories to the CRC has domesticated the convention by passing the Child Rights Act 2003 (CRA) at the national level, for all states of the federation to replicate. However, despite the passage of the CRA and the availability of other legislations and a blueprint educational policy, basic education is not yet a recognised fundamental right under the Nigerian law and consequently not enforceable. This thesis assesses the legal and policy framework on education in Nigeria to see how effective they are in promoting and protecting the right to basic education as a fundamental right of the Nigerian child. To achieve this, qualitative legal research methodology is adopted, by which the thesis analyses the available laws relating to the provision of basic education and the available educational policy in that regard. The same methodology is used to analyse the adequacy or otherwise of the law and policy and semi-structured interview approach is also used to gain the research objectives through responses from the interviewees. Through the analysis of the legal framework, this study finds that the law is weak and inadequate for the recognition of education generally and basic education in particular as a fundamental right, hence, it affects the availability of and accessibility to basic education in Nigeria. The thesis therefore concludes that right to basic education is not recognised under the Nigerian law as an enforceable fundamental right. The thesis also finds that instability and improper implementation of educational policy also affects the provision of compulsory basic education. The thesis further finds that among other factors precluding the protection and promotion of this right are legislative and judicial factors. As a result of these findings, the thesis recommends constitutional reforms, legislative amendments and judicial re-orientation in order to strengthen the legal framework and ensure proper implementation of policy for the recognition, promotion and protection of basic education as fundamental right in Nigeria.